2014
DOI: 10.1136/bcr-2014-204780
|View full text |Cite
|
Sign up to set email alerts
|

The role of palliative rehabilitation in the preservation of personhood at the end of life

Abstract: SUMMARYProgressive advancements in the fields of medicine, oncology and palliative care have seen significant gains in the life expectancy but have also resulted in patients living longer with the burdens of cancer. It is within the sphere of end-of-life care that the role of palliative rehabilitation comes into its own in addressing the effects of increased physical and psychological morbidity that accompany many of these prognostic gains. Focusing on the cancer journey, we highlight the impact of rehabilitat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 11 publications
0
21
0
Order By: Relevance
“…However, activities may not be the best intervention if the client is not motivated. Krishna, Yong and Koh stated that palliative rehabilitation is not effective for all clients and must be seen from a holistic perspective [21]. Future research should examine the team members’ knowledge about the occupational therapist’s role in the multidisciplinary team in order to alert the group as to when occupational therapy is needed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, activities may not be the best intervention if the client is not motivated. Krishna, Yong and Koh stated that palliative rehabilitation is not effective for all clients and must be seen from a holistic perspective [21]. Future research should examine the team members’ knowledge about the occupational therapist’s role in the multidisciplinary team in order to alert the group as to when occupational therapy is needed.…”
Section: Discussionmentioning
confidence: 99%
“…Clients often want to maintain or improve their independence [17, 22, 23], physical function [16, 24], and activities of daily living [10, 17, 2224] in order to live as normally as possible [3, 11, 16, 17, 22]. They want to be able to spend time with their loved ones [4, 6, 11, 16, 17, 19, 21] and possibly to be able to return home [22]. They also want meaningful activities to fill the day [6, 7, 19] and to feel hope [20].…”
Section: Introductionmentioning
confidence: 99%
“…The early initiation and integration of palliative rehabilitation in a patient with life-limiting disease at all phases of their disease trajectory would be an important weapon at helping them to retain their individuality and personhood. [ 10 ] The personalized palliative rehabilitation is tailor made, each stitch attempting to bring together the individual the patient envisions themself to be, by a process of enablement and patient-centered goal setting.…”
Section: Onclusionmentioning
confidence: 99%
“…Briefly, these clinical studies that involved a total of 250 face-to-face semi-structured interviews of palliative care and oncology patients using locally validated questionnaire on conceptions of personhood found that patients consistently held that their personhood or their conception of “what makes you, you” pivots on four domains (Figure 1). 68 73 The first domain is Innate Personhood, which reflects the patient’s ties with God and their genetic identity that defines them as human. 68 73 This domain persists for as long as the patient is alive and ensures that the patient is always treated as a human being and in accordance with prevailing sociocultural beliefs and clinical, societal, institutional, and legal standards that ensure that their rights and interests are protected.…”
Section: Relational Autonomy Frameworkmentioning
confidence: 99%
“…68 73 The first domain is Innate Personhood, which reflects the patient’s ties with God and their genetic identity that defines them as human. 68 73 This domain persists for as long as the patient is alive and ensures that the patient is always treated as a human being and in accordance with prevailing sociocultural beliefs and clinical, societal, institutional, and legal standards that ensure that their rights and interests are protected. 68 73…”
Section: Relational Autonomy Frameworkmentioning
confidence: 99%